PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK BERKESULITAN BELAJAR MELALUI INKLUSI MODEL KLUSTER - pamungkas, bayu (program Studi Pendidikan Luar Biasa FKIP Universitas Sebelas Maret, 2013)
Bayu Pamungkas. INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING APPROACHES TOWARD THE ELEMENTARY READING ABILITY OF CHILDREN WITH LEARNING DISABILITY THROUGH CLUSTER. Thesis, Surakarta : Teacher Training and Education Faculty Sebelas Maret University Surakarta, May. 2013. This research?s aim is to find out influence of the Contextual Teaching and learning approach toward elementary reading ability of chlidren with learning disability through cluster inclusion at SD Alfirdaus Surakarta in 2012/2013 academic year. The used method in this research is experimental method with experiment design called ?One group pretest ? posttes design?. It is a group of subjects which are treatment?s influence is measurement. The population in this research is the students with learning disability at SD Alfirdaus Surakarta in 2012/2013 academic year. Sample in this research is 3 students with learning disability of reading in first grade of SD Alfirdaus Surakarta with pull out in cluster inclusion. Test Technique and documentation is used in colleting data technique. An practice test is used to measure the start reading ability. This research uses statistic non ? parametrix analysis method. This method is Wilcoxon Signed rank tes with the help of SPSS 16. Research conclusion says that there is a significant influence of Contextual Teaching and Learning approaches toward the elementary reading ability of children with learning disability through cluster inclusion at SD Alfirdaus in 2012/2013 academic year. Keywords: Contextual Teaching and Learning, Elementary Reading, Children with Learning Disability, Cluster Inclusion.